Repeated hypoxic episodes allow hematological and physiological habituation in rainbow trout - Ruiz, Nuria; García-Meilán, Irene; Khansari, Ali Reza; Teles, Mariana; Pastor, Josep; Tort, Lluís (Frontiers in Physiology, 2024)
Under climate change the increase of temperature in aquatic environments may induce oxygen depletion. In extreme cases, low oxygen may become a limiting factor for fish, thus generating stress. In addition, consecutive hypoxic episodes may complicate the recovery of individuals and hinder their ability to modulate physiological and biochemical responses to maintain homeostasis.Thus, the aim of this study was to determine the hematological and physiological responses of rainbow trout under a condition of repeated hypoxic and manipulation stress at three different time points. Every hypoxic episode consisted in exposing the fish to low dissolved oxygen concentrations (2 mgO 2 /L for 1 hour). Following the exposure, the fish were allowed to recover for 1 hour after which fish were sampled to investigate hematological and physiological parameters.The results showed a pattern of habituation reflected by values of hematocrit, hemoglobin and mean corpuscular volume, indicating a certain ability of rainbow trout to resist this type of repeated hypoxic events, provided that fish can have some recovery time between the exposures.